2021
DOI: 10.32601/ejal.911458
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Attitudes to Syrian Refugee Students in Turkey

Abstract: From the last decade on, the matter of refugees in Turkey has become a key issue in almost all social and political areas including education. Following the refugee influx from 2011 on, Turkey has immediately taken action to provide the Syrian refugee students with necessary educational opportunities in its mainstream schools. The present study was targeted at revealing Turkish teachers' attitudes towards these Syrian refugee students in their classrooms. A total of 95 in-service teachers from different fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
(13 reference statements)
0
0
0
1
Order By: Relevance
“…Lordoğlu ve Aslan'ın (2018) Türkiye'deki Suriyeli işçi çocuklara dair yaptığı araştırmada da okula devam eden çocukların iyi Türkçe konuştuklarını ifade etmesi bizim araştırmamızın bu yöndeki bulgularını destekler niteliktedir. Türkiye'de bulunan Suriyeli öğrencilere yönelik öğretmen tutumlarının incelendiği bir araştırmada ise öğretmenlerin, göçmen çocukların dil ile ilgili problemlerini çözmede istekli olduğu sonucu ortaya çıkmıştır (Ekin ve Yetkin, 2021). Bu bulgu, dil problemleri konusunda okula gitmeyi işlevsel bir çözüm yapan faktörün, öğretmenlerin bireysel çabası olabileceğini göstermektedir.…”
Section: Discussionunclassified
“…Lordoğlu ve Aslan'ın (2018) Türkiye'deki Suriyeli işçi çocuklara dair yaptığı araştırmada da okula devam eden çocukların iyi Türkçe konuştuklarını ifade etmesi bizim araştırmamızın bu yöndeki bulgularını destekler niteliktedir. Türkiye'de bulunan Suriyeli öğrencilere yönelik öğretmen tutumlarının incelendiği bir araştırmada ise öğretmenlerin, göçmen çocukların dil ile ilgili problemlerini çözmede istekli olduğu sonucu ortaya çıkmıştır (Ekin ve Yetkin, 2021). Bu bulgu, dil problemleri konusunda okula gitmeyi işlevsel bir çözüm yapan faktörün, öğretmenlerin bireysel çabası olabileceğini göstermektedir.…”
Section: Discussionunclassified
“…An analysis of RBSs' experiences in public schools indicated that the major roadblock in teaching RBSs was the communication problem between teachers and RBSs (Arslan & Ergul, 2022;Atalay et al, 2022;Bozkırlı et al, 2018;Ekin & Yetkin, 2021;Ergen & Şahin, 2019;Kaya & Ok, 2021;Kocak et al, 2021;Yiğit et al, 2021). Teachers expressed that they struggled to build background knowledge, deliver the content, explain the activity instructions, and clarify the confusing items due to RBSs' limited Turkish proficiencies (Ergen & Şahin, 2019;Kaya & Ok, 2021;Yiğit et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…To increase teachers' efficiencies in teaching RBSs and RBSs' academic success, in-service teachers were offered training such as psycho-education or multicultural education training by the TMoNE (2022) and international projects (e.g., Erasmus projects such as REFUGEEClassAssistance4Teachers). However, these initiations could slightly increase teachers' self-efficacies or RBSs' school achievement (Ekin & Yetkin, 2021). We believe that pre-service teachers also need training in teaching RBSs so that the training can have wider and longer impacts and increase equity in the Turkish education system.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…These are examined in the context of school-related immigration and acculturation research (see Hachfeld and Syring, 2020). One focus of the research has been on teachers' attitudes toward pupils who have fled Syria (Ekin and Yetkin, 2021). Ekin and Yetkin summarize the research findings available for Turkey as follows: Language problems, pupil and teacher adjustment problems, and inadequate training related to refugee education were reported by teachers.…”
Section: Introductionmentioning
confidence: 99%